Penerapan Model TPS Berbantu Wordwall Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa SMKN 1 Medan - Hasibuan, Layla; Ramdhansyah; La Hanu; Andri Zainal; Ulfa Nurhayani (Jurnal Serambi Ilmu, 2025)
Abstrac This study focuses on the lack of student participation during learning activities and the achievement of expected learning values. learning activities and the achievement of expected learning values. The main objective of the study is to illustrate the extent to which the Think Pair Share (TPS) learning model, supported by Wordwall media, can optimize student activity and learning outcomes. The "Think Pair Share" (TPS) learning model, supported by Wordwall media, can optimize the activity and learning outcomes of all students, particularly in the area of ​​financial statements. all students, particularly in the area of ​​financial statements. This study is a type of (PTK) conducted in two cycles, each cycle consisting of the planning, implementation, observation, and reflection phases, implementation, observation, and reflection. The subjects of this study were 36 students from Class X, AKL 1, SMKN 1, Medan. The data collection method was conducted through observation and testing. The results showed that average student activity increased from 72.10% in the first cycle to 85% in the second cycle. Furthermore, the level of achievement of the comprehensive learning outcomes also increased, from 66.67% to 100%. This data supports the conclusion that using the TPS model with the help of Wordwall media is effective in improving learning outcomes. Using the TPS model with the help of Wordwall media is effective in increasing activity and learning outcomes. Keywords : Think Pair Share (TPS), Wordwall, Learning Activity, Learning Outcomes, Financial Statements